The role of heavy minerals in the thermal maturation of the woodford shale, Anadarko Basin, Oklahoma - Coddington, Kacee (Kansas State University, 2013)
Shales are generally regarded as organic rich source and seal rocks that are unworthy of the amount of research that has been given to their coarser-grained counterparts, even though shales comprise nearly two-thirds of Earth’s sedimentary record (Potter et al., 1980). The Woodford Shale is acknowledged as a prolific source rock across much of Oklahoma and the midcontinent (Lambert, 1990). Up to 8% world's original hydrocarbon reserves are estimated to have been sourced by the Woodford and its equivalents (Fritz et al., 1991). Study of the heavy-mineral fraction in sedimentary rocks is important because it can indicate provenance and some of the diagenetic changes that occur in sedimentary rocks. This goal of this study is to describe the heavy-mineral fraction of eight Woodford Shale samples from the Greater Anadarko Basin of Oklahoma, and determine whether or not the constituents that make up the heavy-mineral fraction have any impact on the process of thermal maturity within source rocks. This study utilizes a method designed to efficiently separate the heavy-mineral fraction of shale samples. Scanning electron microscope (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) are used in this study to identify mineralogy, grain size, composition and shape. Mineral distributions in the samples have been determined from point counting. The weight percent of the heavy mineral fraction was calculated for each of the samples. This was then compared to their location within the basin, depth, vitrinite reflectance and total organic carbon (TOC). We found that as the thermal maturity increase, the weight percent of heavy minerals also increases. Pyrite (FeS₂) was the most abundant heavy mineral found in the Woodford samples used in this study. From analyzing the different forms of pyrite, it was found that as thermal maturity increases, framboidal pyrite alters to euhedral pyrite.
Keywords: Woodford Shale; Source Rock; Heavy Mineral Study; Pyrite; Diagenesis; Thermal Maturation; Geology (0372)